Deslocamento Yanomami para as cidades - Araújo, Adriele Nayara do Nascimento (2020)
This research aimed to discuss the causes of the displacement of Yanomami Indians from their communities to the city of Boa Vista-RR, but also the consequences of the Yanomami presence on the outskirts of a large city such as the capital of the state of Roraima. It is in a scenario of struggle, whose background is the image of the Yanomami indigenous person wandering the streets of Boa Vista that I find support to start a research focused on the indigenous issue. For this purpose, an ethnography on the Yanomami was initially carried out in order to understand its dynamics of experience. In an attempt to understand the origins of this displacement process and insertion in non-indigenous society, the compulsory displacement analysis category was used to justify the Yanomami presence in the city. Finally, the work found the omission of the state and indigenous agencies about the Yanomami both in the community and in an urban context.